Post-World War II Jazz in Britain: Venues and Values 1945–1970 - Williams, Katherine Ann (Jazz Research Journal, 2014)
This article explores the ways in which jazz was presented and mediated through venue in post-World War II London. During this period, jazz was presented in a variety of ways in different venues, on four of which I focus: New Orleans-style jazz commonly performed for the same audiences in Rhythm Clubs and in concert halls (as shown by George Webb’s Dixielanders at the Red Barn public house and the King’s Hall); clubs hosting different styles of jazz on different nights of the week that brought in different audiences (such as the 100 Club on Oxford Street); clubs with a fixed stylistic ideology that changed venue, taking a regular fan base and musicians to different locations (such as Ronnie Scott’s Jazz Club); and jazz in theatres (such as the Little Theatre Club and Mike Westbrook’s compositions for performance in the Mermaid Theatre).